The effect of midwifery-led counseling on expectant fathers' fear of childbirth: a smartphone- based randomized controlled trial - Seyedeh Fatemeh Ghaffari; Forouzan Elyasi; Seyed Nouraddin Mousavinasab; Zohreh Shahhosseini (BMC, 2022)
Abstract Background Expectant fathers experience a range of different emotions during their wife's pregnancy; one of these feelings is fear. It has adverse consequences on both the father and his family. The aim of this study was to investigate the effect of midwifery-led counseling on the fear of childbirth among expectant fathers. Methods A two-armed parallel design randomized controlled trial was conducted from July to August 2020. Fifty expectant fathers with severe fear of childbirth at the 24th-27th weeks of gestation, in the Iranian setting, were assigned to intervention and control groups (allocation ratio1:1) using permuted block randomization. Participants assigned to the intervention group were engaged in six 60-90-min midwifery-led counseling sessions (twice a week) in the Skyroom platform. Measures were administered at recruitment, post-intervention, and one-month follow-up. The primary outcome was the change in fear of childbirth score between groups over time. Secondary outcomes were changes in the General Self-Efficacy score as well as changes in the frequency of the preferred type of delivery between groups over time. Results The mean age of the participants was 31.64 (3.33) years. In the intention-to-treat analysis, the fear of childbirth score in the intervention group significantly decreased (β = − 11.84; 95% Confidence Interval: − 21.90 to − 1.78; P = 0.021) compared to that of the control group. In terms of secondary outcomes, the intervention group showed a significant increase in General Self-Efficacy compared to the intervention group at one-month follow-up measurement (β = 1.43; 95% Confidence Interval: 0.28 to 2.58; P = 0.014). However, the frequency of preferred delivery type was not significantly different between the intervention and control groups (P = 0.139). Conclusions Midwifery-led counseling can be an effective approach in reducing expectant fathers' childbirth fear with potential clinical significance. Although the inconclusive results imply more research on this issue. Trial registration Registration number: IRCT20150608022609N6 . Registered 12/04/2019.